La inevitable flexibilidad de las condiciones laborales - Dilla Catalá, Mª José; Sobrino González, Gemma Mª (Cuadernos de Relaciones Laborales, 2008)
The current productive system requires an increasing flexibility of working conditions. This way, working conditions can be adapted to the changing necessities of the labour market. Within this context, Collective Bargaining plays a crucial role. In this article we analyse the role played by the Collective Agreements in terms of working hours and non-substiantial functional mobility of workers. In terms of functional mobility, such Agreement will be analyzed in terms: the structuring of professional classification system, the upward and downward mobility, the polyvalence, and the used mechanism aimed at excluding certain mobility trends. Concerning working time, aspects analyzed are those on which flexibility have had a bigger impact, such as the length of the working day, the irregular layout of working time around the year, the daily and weekly rest. Finally a special reference is done to overtime work.